Depositional Record and Geochemistry Constraints on the Late Miocene–Quaternary Evolution of the Taiyuan Basin in Shanxi Rift System, China - Zhuang, Qitian; Wei, Rongzhu; He, Honglin (Frontiers in Earth Science, 2022)
The formation and evolution of the Shanxi Rift System are topics of interest because of its unique geometry and critical position in the North China Plate. However, it is not easy to delineate the late Cenozoic tectonic processes. This is partly because the normal faults are difficult to preserve their movement evidence and related deposits for dating in the outcrop. Besides, the current studies are heavily weighted in the low-temperature thermochronology, whereas it is insensitive to the exhumation after the late Miocene. To decipher the late Cenozoic evolution, we offer a case of detailed depositional recording from the boreholes of the Taiyuan Basin in the Shanxi Rift System. Fluvial, deltaic, and lacustrine environments were identified by the systematic stratigraphic analysis of boreholes. Two great transgressions generated basin-wide lakes at ca. 5.8–4.4 Ma and ca. 2.2–1.6 Ma. We attribute the lake expansion events to tectonism because reconstruction of the paleoclimate with geochemistry index and regional climatic variations in the same period indicated asynchronous processes with the transgression. Thus, the basin experienced at least two great tectonic movements after the rift occurred. This result is conducive to obtaining a more complete late Cenozoic tectonic evolution of the Shanxi Rift System.